STUDY OF THE DEVELOPMENTAL STATUS OF SCHEDULED TRIBES IN INDIA - J. V. Padvi (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The present study examines the developmental status of Scheduled Tribes (STs) in India, focusing on their socio-economic conditions, educational progress, health indicators, and overall quality of life. Scheduled Tribes, being one of the most marginalized and disadvantaged communities in India, have historically faced challenges related to poverty, illiteracy, poor health infrastructure, and social exclusion. This paper aims to analyze various government initiatives, constitutional provisions, and developmental programs implemented for the upliftment of tribal communities. The study highlights regional disparities, identifies key barriers to development, and evaluates the effectiveness of policies and schemes in bridging the gap between Scheduled Tribes and the mainstream population. Through a critical assessment of secondary data and reports, the paper also explores issues like displacement, land alienation, and cultural erosion faced by tribal groups. The findings of the study suggest that while progress has been made in certain areas, significant challenges remain in achieving inclusive and sustainable development for Scheduled Tribes in India.